Effect of Feeding Pellets Containing Different Concentrate to wheat Straw Ratios on the Rumen Fermentation Characteristics of Awassi Lambs (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was carried out in Alsiyahii area– Babylon Province to investigate the effect of feeding Awassi lambs different ratios of concentrate: wheat straw (C: R) on rumen fermentation characteristics. Five pellets of total mixed rations (TMR) containing 30:70, 40:60, 50:50, 60:40 and 70:30 of C: R ratios were prepared and offered to lambs ad libitum. Results revealed that increasing C: R ratio was associated with a significant (P